Цифрові технології організації обліку в банках - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Сіренко, Н. М.; Sirenko, N.; Мікуляк, К. А.; Mikuliak, K. (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2025)
Авторами статті досліджуються цифрові технології організації обліку в комерційних банках. Висвітлені основні теоретичні аспекти поняття та цілі банківського обліку, а також особливості його організації з врахуванням сучасних цифрових технологій. Визначені основи і завдання банківсько-го обліку та його значення в умовах цифровізації економіки. Відзначено, що організація обліку в банках має низку відмінностей у порівнянні з підприємствами інших галузей і має свою структурну побудову. Відокремлено переваги цифрових технологій в банківському обліку. В статті здійснено порівняльну характеристику обліку у банках до і після цифровізації. Отже, цифрові технології кардинально змінюють підходи до організації обліку в банках. В умовах динамічних змін регуляторного середовища, зростання конкуренції та підвищених очікувань клієнтів, цифровий облік стає критично важливим елементом для забезпечення конкурентоспроможності та стабільності банку. he article explores digital technologies for organizing accounting in commercial banks. The main theoretical aspects of the concept and goals of bank accounting are highlighted, as well as the features of its organization taking into account modern digital technologies. The foundations and tasks of bank accounting and its significance in the conditions of digitalization of the economy are determined. It is noted that the organization of accounting in banks has a number of differences compared to enterprises in other industries and has its own structural structure. The advantages of digital technologies in bank accounting are highlighted. The article provides a comparative characteristic of accounting in banks before and after digitalization. Thus, digital technologies are radically changing approaches to organizing accounting in banks. They allow you to create effective, accurate, safe and flexible accounting systems. At the same time, it is important to take into account the challenges of digitalization and adapt banking structures to new conditions, investing in security, infrastructure and personnel training. Digital technologies do not just modernize accounting in banks — they become the basis of a new model of banking activity, where data and technologies act as fixed capital. In the face of dynamic changes in the regulatory environment, increasing competition, and heightened customer expectations, digital accounting is becoming a critically important element for ensuring the competitiveness and stability of a bank. However,the implementation of digital technologies requires not only investments in IT solutions, but alsoreorganization of internal processes, changes in corporate culture and continuous training of personnel.It is the combination of innovation and human capital that ensures effective digital transformation of bankaccounting. Considering the experience of Ukrainian banks, it is safe to say that in the digital economy,banks that actively implement the latest accounting technologies gain a significant competitive advantageand are able to quickly adapt to the challenges of the modern market
Digital technologies for organ izing accounting in banks bank
Keywords: фінансові інжиніринг; financial engineering; активи; assets; управління активами; asset management; аграрні підприємства; agricultural enterprises; продовольча безпека; food security